Postoperative Progress after Stone Removal Following Treatment for Obstructive Acute Pyelonephritis Associated with Urinary Tract Calculi: A Retrospective Study - Yamashita, Shimpei; Kohjimoto, Yasuo; Higuchi, Masatoshi; Ueda, Yuko; Iguchi, Takashi; Hara, Isao (Urology Journal, 2020)
Purpose: We aimed to identify the prevalence and risk factors of three outcomes after stone removal following treatment for obstructive acute pyelonephritis (APN) associated with urinary tract calculi: immediate postoperative febrile urinary tract infection (UTI), stone recurrence, and APN recurrence during the follow-up period. Materials and Methods: We retrospectively reviewed the charts of 107 patients who underwent stone removal following treatment for obstructive APN associated with urinary tract calculi. Logistic regression analysis was used to identify the factors that contributed to postoperative febrile UTI after stone removal. Cox proportional hazard analyses were used to identify the factors contributing to stone recurrence and APN recurrence during the follow-up period. Results: Postoperative febrile UTI was observed in 23 out of 107 patients (21.5%). Multivariate logistic regression analysis revealed that female sex (P = .02) and having multiple stones (P < .01) were independently significant predictors of postoperative febrile UTI. One-year recurrence-free survival rates of stone disease and APN were 76.1% and 82.5%, respectively. Multivariable cox proportional hazard analyses revealed that presence of residual fragments was the only significant risk factor for stone recurrence (P < .01) and marginally significant for APN recurrence (P = .05). Conclusion: Patients presenting with obstructive APN frequently develop postoperative febrile UTI after active stone removal with the risk factors being female sex and having multiple stones. Residual fragments after stone removal in patients with obstructive APN can cause urolithiasis and APN recurrence, indicating that complete removal of stone fragments ? 4 mm is imperative to the disease management.